2005
DOI: 10.1007/s11095-005-6250-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Pharmacological Properties of Rutin, a Dietary Quercetin Glycoside, for Treatment of Inflammatory Bowel Disease

Abstract: Our data suggest that rutin acted as a quercetin deliverer to the large intestine and its anti-inflammatory action in TNBS-induced colitis rats may be through quercetin-mediated inhibition of TNF-alpha-induced NFkappaB activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(101 citation statements)
references
References 36 publications
6
95
0
Order By: Relevance
“…In our previous report, we suggested that quercetin-mediated amelioration of rat colitis was elicited by inhibiting NFB activity (Kim et al, 2005). Our data demonstrating quercetin activation of HIF-1-VEGF pathway in cells and inflamed colonic tissue suggest that quercetin exerts its clinical effect by not only inhibiting the inflammatory signal but also activating the tissue repair signal.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In our previous report, we suggested that quercetin-mediated amelioration of rat colitis was elicited by inhibiting NFB activity (Kim et al, 2005). Our data demonstrating quercetin activation of HIF-1-VEGF pathway in cells and inflamed colonic tissue suggest that quercetin exerts its clinical effect by not only inhibiting the inflammatory signal but also activating the tissue repair signal.…”
Section: Discussionmentioning
confidence: 51%
“…We reported previously that quercetin is effective in ameliorating TNBS-induced rat colitis, and the clinical effect is elicited by at least partly inhibiting a major pro-inflammatory NFB pathway (Kim et al, 2005). To explore an additional pharmacological mechanism of the quercetin effect on experimental colitis, we investigated whether quercetin, in addition to suppressing an inflammatory signal, could stimulate a tissue repair signal, which accelerates healing of inflammatory injury.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of polyphenols was effective at preventing and treating intestinal inflammation in rodents models of IBD where acute or chronic colitis was induced by intrarectal administration of dinitrobenzene sulphate (Oz et al, 2005, Kim et al, 2005 and addition of dextran sulphate sodium (DSS) to drinking water (Camuesco et al, 2004 (Wang et al, 2008, Elmali et al, 2007, Tang et al, 2007.…”
Section: Moderation Of the Inflammatory Response In Colorectal Cancermentioning
confidence: 99%